Assessing the immovable asset data quality: The critical role of people, process, and technology across public sector - Mahamad Subri, Mohd Suharizal; Ngah Nasaruddin, Afiqah; Sapri, Maimunah; Abdullah Hashim, Hariati; Md Fadil, Madihah; Abd Malek, Mohamad Adzizulrohim; Tee, Boon Tuan (Construction Research Institute of Malaysia, 2025)
This paper explores the quality of immovable asset data across public sectors, focusing on the interdependent roles of people, processes, and technology. Note that high-quality data is essential for effective asset management, policy–making, and service delivery. However, ensuring data quality in the public sector presents unique challenges due to the complex and often fragmented nature of public sector operations. This research identifies key factors influencing data quality in public sector asset management and proposes a comprehensive framework for assessing and improving immovable asset data quality. The study combines literature reviews, case studies, and expert interviews to provide a holistic understanding of the critical role of people, processes, and technology in achieving high-quality immovable asset data. Therefore, ensuring the quality of immovable asset data is a critical challenge for public sector organizations. Immovable assets, such as buildings, roads, and infrastructure, are foundational to public service delivery and economic development. Effective management of these assets relies heavily on data accuracy, completeness, and reliability. Moreover, poor data quality can lead to suboptimal decision-making, increased costs, and inefficiencies in asset utilization and maintenance. This research paper investigates the factors influencing data quality in public sector immovable asset management, focusing on the critical roles of people, processes, and technology.